2011
DOI: 10.3109/08039488.2011.565799
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the metabolic syndrome in Danish psychiatric outpatients treated with antipsychotics

Abstract: The metabolic syndrome is highly prevalent among a Danish outpatient population treated with antipsychotics compared with the general population. Monitoring of lipid and glucose levels, blood pressure and waist circumference before start-up and during treatment with antipsychotic medication is of pivotal importance in order to prevent diabetes and cardiovascular disease in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…The findings of our study are in line with other studies done previously. 30,31 Our study showed that the patients under treatment of olanzapine were more prone to develop metabolic syndrome as compared to the patients taking risperidone treatment.…”
Section: As Per the International Diabetes Federation (Idf 2006) Critmentioning
confidence: 73%
“…The findings of our study are in line with other studies done previously. 30,31 Our study showed that the patients under treatment of olanzapine were more prone to develop metabolic syndrome as compared to the patients taking risperidone treatment.…”
Section: As Per the International Diabetes Federation (Idf 2006) Critmentioning
confidence: 73%
“…Table 4. The number and prevalence of metabolic syndrome (MS) with age and sex of the participants For comparison with other Danish samples, the prevalence of MS among 3,303 persons in the general Danish population was calculated to 29.6% [27]. In another Danish population sample with a median age of 51 (41-74) years studied, the prevalence of MS based on the International Diabetes Federation criteria was 23.8 for men and 16.1 for women [28].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to other studies which showed prevalence rates of 48% for the metabolic syndrome in individuals treated with antipsychotics. 14 Strengths of the study are the screening of a cohort attending day centres in a catchment area service and thus representative of patients with chronic enduring mental illness in the region, rather than confined to a particular diagnosis or type of medication.…”
Section: Discussionmentioning
confidence: 99%